Neurologic outcomes of pediatric epileptic patients with pentobarbital coma - Kim, Sun Jun; Lee, Dae Yeol; Kim, Jung Soo (Pediatric neurology, 2001)
Status epilepticus is a life-threatening condition requiring emergent medical attention. Although initial therapies with antiepileptic drugs generally terminate seizures within 30 to 60 minutes, patients with refractory status epilepticus require additional intervention. High-dose pentobarbital has been the most commonly prescribed agent for the management of refractory status epilepticus in children. The objective of this research was to evaluate the association between the response of pentobarbital coma and neurologic outcomes in refractory status epilepticus. Twenty-three subjects were treated with pentobarbital coma for at least 48 hours. Medical records were reviewed to collect patient demographic information, responses to treatment, and neurologic outcomes. Among the 23 patients reviewed, 12 patients were controlled with pentobarbital (responders), six were unresponsive to pentobarbital (nonresponders), and five patients relapsed after discontinuation or during tapering of pentobarbital (relapser). The mortality rate among the relapser and nonresponder groups combined was 90.9%, but no deaths occurred among the responder group ( P < 0.001). The survival rate was greater among toddlers compared with neonates or older children. Failure of seizure control after pentobarbital coma was associated with a poor prognosis. The potential for serious complications of pentobarbital therapy among neonates highlights the need for careful dosing in this age group.